Ovarian SAHA syndrome is associated with a more insulin-resistant profile and represents an independent risk factor for glucose abnormalities in women with polycystic ovary syndrome: a prospective controlled study. - Dalamaga, Maria; Papadavid, Evangelia; Basios, Georgios; Vaggopoulos, Vassilios; Rigopoulos, Dimitrios; Kassanos, Dimitrios; Trakakis, Eftihios (J Am Acad Dermatol, 2013)
BACKGROUND: SAHA syndrome is characterized by the tetrad: seborrhea, acne, hirsutism, and androgenetic alopecia. No previous study has examined the prevalence of glucose abnormalities in ovarian SAHA and explored whether it may be an independent risk factor for glucose abnormalities. OBJECTIVE: In a prospective controlled study, we investigated the spectrum of glucose abnormalities in ovarian SAHA and explored whether it is associated with a more insulin-resistant profile. METHODS: In all, 316 patients with a diagnosis of polycystic ovary syndrome (PCOS) (56 with SAHA) and 102 age-matched healthy women were examined and underwent a 2-hour oral glucose tolerance test. Serum glucose homeostasis parameters, hormones, and adipokines were determined. RESULTS: SAHA prevalence was 17.7% in patients with PCOS and predominance of the severe PCOS phenotype. Ovarian SAHA was independently associated with a more insulin-resistant profile (higher homeostatic model assessment of insulin resistance score, lower quantitative insulin sensitivity check index [QUICKI] and MATSUDA indices, and relative hypoadiponectinemia), and represented an independent risk factor for glucose abnormalities regardless of anthropometric features, age, and PCOS phenotype. LIMITATION: There was no performance of skin biopsies. CONCLUSION: The prompt recognition of SAHA syndrome in women with PCOS permits an earlier diagnosis and surveillance of metabolic abnormalities, especially in Mediterranean PCOS population exhibiting a lower prevalence of glucose abnormalities.
Keywords: Acne Vulgaris; Adolescent; Adult; Alopecia; Dermatitis, Seborrheic; Female; Glucose; hirsutism; Humans; Insulin Resistance; Ovarian Diseases; Polycystic ovary syndrome; Prospective Studies; Risk Factors; Syndrome; Young Adult